Experimental investigations on physico-mechanical properties of kaolinite clay soil stabilized at optimum silica fume content using clamshell ash and lime - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Almuaythir, Sultan; Hyodo, Masayuki (Nature Publishing Group, 2024)
This investigation examines the effect of clamshell ash (CSA) and lime additives on the physico-mechanical characteristics of kaolinite clay soil stabilized at the optimum silica fume content. Laboratory tests were performed to assess plasticity, shrink-swell characteristics, compaction characteristics, unconfined compressive strength (UCS), shear strength characteristics, mineralogical and morphological microstructure characteristics of stabilized soil specimens. The kaolinite clay soil was stabilized at its optimum silica fume content (6%) to produce the highest strength and was altered with three non-identical proportions of clamshell ash and lime (3%-9%). Cylindrical soil specimens, 76 mm in height and 38 mm in diameter, were moulded and treated for curing periods of 1, 7, 14, and 30 days to examine the strength of the altered soil. The findings revealed that, adding clamshell ash and lime significantly alters the plasticity, shrink-swell, maximum dry unit weights, and optimum moisture contents of the silica fume-stabilized soil. In terms of strength, the beneficial effects of CSA and lime additives were found to be more significant with more extended curing periods. Incremental increases in curing periods resulted in further enhancements in UCS, cohesion, and internal friction angle, indicating continued strength development over time. Microstructural analysis using field emission scanning electron microscopy and X-ray diffraction provided insights into the interparticle bonding mechanisms and microstructural changes induced by the addition of CSA and lime. The emergence of cementitious phases and pozzolanic responses between soil particles and stabilizers contributed to the densification and strengthening of the stabilized soil matrix. The findings of this study provide valuable insights into the potential of clamshell ash and lime additives to enhance the engineering properties of kaolinite clay soil stabilized with silica fume. These results have implications for sustainable soil stabilization practices, offering a promising approach to improve the performance of soils for various engineering applications, including construction and geotechnical projects.